1074The role of epidemiology in improving the health of people with disability. (2nd September 2021) - Kavanagh, Anne; Fortune, Nicola; Disney, George; Aitken, Zoe; Badji, Samia
Abstract: Focus and outcomes for participants: The symposium will focus on the role of epidemiologists in building an evidence base to improve the health of the 15% of the world's population with disability who currently experience vast health inequalities. Participants will be introduced to new ways of conceptualising disability in epidemiology; state of the art approaches to monitoring disability-related socio-economic and health inequalities; methodological challenges and solutions to address the biases due to misclassification, confounding and reverse causation; and the application of causal mediation analysis and natural experiments in identifying potential policy solutions. Participants will gain a greater understanding of how epidemiological methods can be applied to improve the health of people with disability, as well as insights and ideas for their research. A network of epidemiologists interested in this topic will be generated to foster ongoing communication and collaborative opportunities. Rationale for the symposium, including for its inclusion in the Congress: The health of disabled people has largely been ignored by epidemiologists. This is despite emerging evidence that people with disability experience poorer health because of factors unrelated to their impairment, including socio-economic disadvantage, discrimination, and violence. However, turning epidemiologists' efforts to the health of people with disability presents conceptual and methodological challenges, some of which are unique to the content area. Participants will be shown a suite of approaches that can be deployed to address these problems. Participatory methods and innovative graphical and statistical methods for analysing disability-related health inequalities, approaches rarely used in epidemiology, will be covered. The symposium will also concentrate on the application of methods to optimise causal inference in the presence of multiple potential biases, and methods that simulate randomised controlled trial conditions to model policy interventions. Presentation program: The presentations are from researchers from the CRE-DH, funded through Australia's National Health and Medical Research Council organised four themes. Theme 1: Conceptualisation of disability We will present findings from a scoping review of original articles in epidemiology journals and will argue that, while, disability is usually conceptualised in epidemiology as an outcome, reconceiving of disability as an exposure, mediator and/or effect modifier can provide important insights on the determinants of health of people with disability. Theme 2: Monitoring disability-related inequalities We will demonstrate how the CRE-DH has used participatory methods, where people with disability are 'experts through lived experience', to develop indicators to monitor disability-related inequalities and design a National Community Attitudes survey. We will demonstrate innovative ways to graphically illustrate prevalence, absolute and relative inequalities simultaneously, and discuss how hierarchical Bayesian methods can be used to overcome inadequate power due to disaggregation and assess inequalities under uncertainty. Theme 3: Approaches to minimising bias We will talk about how biases can affect estimates of disability prevalence and disability-outcome associations, including reverse causation, confounding and misclassification. We will discuss a range of approaches we have used to address these challenges including modelling incident (rather than prevalent) disability, using fixed effects models and propensity score approaches, and approaches to addressing misclassification bias drawing on examples from our program of research. Theme 4: Identification of policy interventions We will discuss methods that can be used to model the impact of policies on the health of people with disability using examples from our research. We will present the results of a causal mediation analysis modelling the impact of different employment policy interventions on mental health outcomes. We will illustrate the value of natural policy experiments for estimating effects of policy changes on employment and health of people with disability using two examples – the 2014 reassessment of Disability Support Pensioners under stricter impairment tables and the introduction of Australia's National Disability Insurance Scheme. The symposium will conclude with a facilitated discussion focussed on how epidemiologists can come together internationally to grasp the opportunities and address the challenges in research focussed on the health of people with disabilities. Names of presenters: Professor Anne Kavanagh, PhD Dr Nicola Fortune, PhD Dr George Disney, PhD Dr Zoe Aitken Dr Samia Badji, PhD